'The Open Whole': Human-Nonhuman Relationality in Carlos Reygadas' Neo-Surrealist Post Tenebras Lux (2012)*. Issue 1 (2nd January 2017) - Bollington, Lucy
Abstract: This article reads Carlos Reygadas' neo-surrealist film Post Tenebras Lux in dialogue with Eduardo Kohn's anthropological text How Forests Think: An Anthropology beyond the Human in order to interrogate the human-nonhuman relationality that characterizes Reygadas' filmmaking. I examine the ways Reygadas' and Kohn's works intersect around themes of semiosis, dreamscapes, death and the relationship between nonhuman worlds and precarious categories of human life. My analysis also attends to the surrealistic elements and antecedents that shape human-nonhuman relationality in Post Tenebras Lux, with particular reference to surrealist celebrations of oneiric spaces and appeals to the reenchantment of a world darkened by reason. My argument is twofold: I demonstrate that, in the surrealist tradition, Reygadas opens up the human to nonhuman ontologies as a means of challenging the legacy of restrictive, rationalistic thought; and in doing so, his film implicitly foregrounds an 'open' form of posthumanism, which works in tandem with human social and existential concerns.